2011
DOI: 10.1039/c0jm02494e
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functionalized graphene oxide based anticancer drug-carrier with dual-targeting function and pH-sensitivity

Abstract: A dual-targeting drug delivery and pH-sensitive controlled release system based on multifunctionalized graphene oxide (GO) was established in order to enhance the effect of targeted drug delivery and realize intelligently controlled release. A superparamagnetic GO-Fe 3 O 4 nanohybrid was firstly prepared via a simple and effective chemical precipitation method. Then folic acid, a targeting agent toward some tumor cells, was conjugated onto Fe 3 O 4 nanoparticles via the chemical linkage with amino groups of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
309
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(320 citation statements)
references
References 25 publications
7
309
1
3
Order By: Relevance
“…26,[28][29][30][31] However, the potential use of GO as a DDS has recently received increased attention. [32][33][34][35] For example, Sun et al not only demonstrated the potential of GO as a DDS for the pH-sensitive release of doxorubicin (Dox) into cancer cells, but also specified the concomitant use of this material as an imaging agent. 34 Regardless of this first proofof-concept, carbon nanotubes and GO lack or have very low fluorescence efficiencies, which limit the tracking of these materials within complex living organisms and even within individual cells.…”
Section: Qiu Et Almentioning
confidence: 99%
“…26,[28][29][30][31] However, the potential use of GO as a DDS has recently received increased attention. [32][33][34][35] For example, Sun et al not only demonstrated the potential of GO as a DDS for the pH-sensitive release of doxorubicin (Dox) into cancer cells, but also specified the concomitant use of this material as an imaging agent. 34 Regardless of this first proofof-concept, carbon nanotubes and GO lack or have very low fluorescence efficiencies, which limit the tracking of these materials within complex living organisms and even within individual cells.…”
Section: Qiu Et Almentioning
confidence: 99%
“…Some functional groups of GO, such as carboxylic acid and hydroxyl groups, can serve as the binding sites with metal ions, and form nuclei surrounding the interaction sites between metal ions and GO, and followed by the growth of nanomaterials around the nucleus (32). For instance, GO/iron oxide composites can be synthesized by the following methods: Fe 3+ /Fe 2+ ions in the proper molar ratio (2:1) were mixed with GO, and then were precipitated by alkaline solutions, such as ammonia solution (NH 3 •H 2 O), and sodium hydroxide (NaOH) (33,34). Besides the coprecipitation strategy of Fe 3+ and Fe 2+ ions under alkaline condition, hydrothermal reaction was also employed to prepare GO/iron oxide composites by using iron chloride hexahydrate as the iron source (30,35).…”
Section: In Situ Growth Methodsmentioning
confidence: 99%
“…2, the peak at 1732 cm −1 is corresponding to C = O stretch of the carboxylic group on GO surface [39]. After the reaction of GO and Fe 3 O 4 -NH 2 , this peak almost disappears, and three new characteristic peaks at 1634 cm −1 ( CONH amide band I), 1568 cm −1 ( NH amide band II), and 575 cm −1 (Fe O stretch) appear [40], implying that Fe 3 O 4 -NH 2 is covalently linked to GO surface via amide reaction. Raman spectrum was also applied to characterize GO and GO-CO-NH-Fe 3 O 4 .…”
Section: Synthesis and Characterization Of Go-co-nh-fe 3 O 4 Nanocompmentioning
confidence: 99%
“…Furthermore, such groups make GO convenient to be modified [31][32][33][34][35][36][37][38]. Recently, GO based magnetic nanocomposites have been widely used in various fields, such as targeted drug carriers [39,40], pollution control [41], and battery materials [42][43][44]. With large surface area and considerable hydrophilic groups, GO is a perfect substrate for enzyme immobilization.…”
Section: Introductionmentioning
confidence: 99%